THE ROLE OF BAKTI GAMIA PRODUCT AS ANEMIA PREVENTION IN PREGNANT WOMEN AT TPMB JAMILA, SOUTH JAKARTA - Lubis, Rita Mahdalena; Rahmayanti, Arini; Siburian, Claranita; Restinah, Anjar; Muslichah, Muslichah; Surtini, Surtini; Silferia, Silferia; Susanti, Dwi; Indirayani, Triana (International Journal of Engagement and Empowerment (IJE2), 2024)
In the initial quarter of 2024, the percentage of pregnant women with anemia receiving ANC at TPMB Jamila in RW. 03 South Jakarta was recorded at 11% (31 individuals out of 279 pregnant women). Addressing this issue, an approach to tackle anemia in pregnant mothers involves education and intervention. This community initiative aims to enlighten pregnant women about the significance of consuming iron-rich foods and enhancing iron absorption to mitigate anemia during pregnancy. The endeavor involves data collection, identifying priority concerns, developing educational materials, and providing product interventions. Evaluation is conducted through discussions and Q&A sessions. A total of 14 pregnant women and 6 additional participants, including lecturers, midwives, and cadres, engaged in the counseling sessions, which were carried out collaboratively with team members. Notably, participants exhibited high levels of enthusiasm and participation throughout the activities